Impact of length of stay on diagnostic yield in the epilepsy monitoring unit: A multi‐center retrospective 12‐year Veterans Health Administration study - Maximillian S. Feygin; Autumn Smith; Sruthi Gopinath Karicheri; Khadar Haroun; Omar Khan; Maria R. Lopez; Stephan Eisenschenk; John Jones; Stephanie Reeder; Alan R. Towne; Christopher Ransom; Karen Medin; et al. (Epilepsia Open)
Abstract Objective Epilepsy Monitoring Units (EMUs) in Veterans Health Administration (VHA) Epilepsy Centers of Excellence (ECoE) are critical for the diagnosis and management of seizure disorders. Whether a shorter length of stay (LOS) in the EMU due to scheduling impacts diagnostic yield is unclear. Methods Data from 7074 EMU visits across 15 VHA EMUs (2012–2024) were analyzed. Based on usual admission schedules, EMUs were divided into “fixed” (typically Monday–Friday) or “flexible” subgroups. Diagnostic outcomes were classified as epileptic seizures (ES), psychogenic non‐epileptic seizures (PNES), other non‐epileptic events, and inconclusive. Diagnostic rates were compared between fixed and flexible sites using cumulative distribution functions and other statistical tests. Readmission data for initially inconclusive cases were also examined. Results Diagnostic outcomes showed the following distribution: 23% ES, 19% PNES, 11% other non‐epileptic events, and 47% inconclusive. Similar distributions were seen between fixed and flexible sites, although a higher proportion of diagnostic admissions were completed earlier in fixed sites and over a longer average LOS at flexible sites. Admissions diagnostic of ES had longer LOS than all other outcomes (4.5 vs. 3.8 days, p < 0.001). Repeat EMU admissions were performed in 10% of patients and were more likely to be diagnostic of ES than PNES or other non‐epileptic events. Significance About half of EMU admissions within VHA were non‐diagnostic with respect to the patients' typical clinical events. ES and PNES were observed at approximately similar rates, although the diagnosis of ES required a longer LOS. Fixed sites did not appear inferior to flexible sites for reaching diagnostic conclusions in our analysis. The higher proportion of earlier diagnoses at fixed sites observed was likely a statistical effect of their predefined shorter admission lengths. Further investigations of EMU resource utilization based on individual goals of monitoring are necessary to better examine and improve efficiency. Plain Language Summary Epilepsy Monitoring Units (EMUs) are specialized hospital units used to diagnose and characterize seizures. This study looked at over 7000 admissions across 15 Veterans Health Administration EMUs to see whether length of stay affected diagnosis rates based on admission scheduling and seizure types. Regardless of whether patients were admitted on a fixed schedule (Monday–Friday) or a flexible schedule, about half of hospitalizations did not capture typical events. Diagnosis of epileptic seizures and psychogenic non‐epileptic seizures occurred at similar rates, though diagnosing epileptic seizures took longer. Findings suggest fixed (shorter) hospital stays may be as effective as longer flexible hospitalizations.